Intake of vegetables and fruits at midlife and the risk of physical frailty in later life - Kevin Yiqiang Chua; Huiqi Li; Li-Ting Sheng; Wee-Shiong Lim; Woon-Puay Koh (Elsevier, 2024)
Objectives: Our study evaluated the independent and overall associations of vegetable and fruit consumption at midlife with the likelihood of physical frailty in later life. We also investigated whether specific nutrients in these foods could have accounted for these associations, if present. Design: Prospective cohort study. Setting: A population-based cohort of Chinese adults followed over a period of 20 years in Singapore. Participants: We used data from 11,959 subjects who participated in the baseline (1993-1998) and follow-up 3 (2014-2017) interviews of the Singapore Chinese Health Study. Measurements: At baseline, dietary intake was evaluated using a validated food frequency questionnaire. During the follow-up 3 visits, physical frailty was assessed using a modified Cardiovascular Health Study phenotype that included weakness, slowness, exhaustion and weight loss. Multivariable logistic regression models were used to estimate odds ratios (OR) and 95% confidence intervals (CI) for the associations with physical frailty. Results: Participants had mean ages of 52 years at baseline, and 72 years at follow-up 3. Baseline intake of vegetables, but not of fruits, showed a dose-dependent inverse relationship with physical frailty at follow-up 3 (Ptrend = 0.001). Compared to participants in the lowest quintile of vegetable intake, those in the highest quintile had reduced odds of frailty [OR (95% CI): 0.73 (0.60−0.89)]. Among the components of physical frailty, vegetable intake had the strongest inverse association with weakness defined by handgrip strength [OR (95% CI) between extreme quintiles: 0.62 (0.52−0.73); Ptrend < 0.001]. In models that were individually adjusted for nutrients, the vegetable-frailty association was attenuated and no longer statistically significant after adjusting for the intake of β-carotene, lutein, folate, α-carotene, and isothiocyanates. Conclusion: : Increased midlife intake of vegetables was associated with reduced odds of physical frailty in later life, and the intake of β-carotene, lutein, folate, α-carotene, and isothiocyanates could have accounted for this association.